Synchronized effect of citric acid and phytase supplementation on growth performance and nutrient digestibility of Labeo rohita. (10th August 2017) - Bano, N.; Afzal, M.
Abstract: A 2‐month trial was conducted to record the effect of citric acid and phytase supplementation on growth performance and nutrient digestibility in labeo rohita . Nine treatment (T) diets having 0, 500 and 1, 000 FTU/KG phytase and 0, 15 and 30 g/kg citric acid were prepared and were designated as T1, T2, T3, T4, T5, T6, T7, T8 and T9 diets. There were three replicates for each of the test diets. Fish samples ( n  = 324) were stocked in different tanks and were fed with T1, T2, T3, T4, T5, T6, T7, T8 and T9 diets. Significant ( p  < .05) increase in growth parameters, apparent digestibility of dry matter, crude protein, crude fat, gross energy and minerals (Na, K, Fe, Mg, Mn, Zn) was recorded in fish fed with T9 diets.